A insurreição contestada: William Styron e As confissões de Nat Turner - Nigro, Cláudia Maria Ceneviva [UNESP] (My University, 2013)
This work presents intricacies of "truth" in the historical novel Confessions of Nat Turner, by William Styron, considering the point-of-view of the novel's narrator. When speaking about the black, Styron somehow keeps the white's perspective, and also perpetuates the distance created by the slavery and segregationist system of the United States of America.

Neste trabalho apresentamos meandros de “veracidade” no romance histórico de William Styron, As confissões de Nat Turner, levando em consideração o ponto de vista do narrador. Ao falar do negro, Styron mantém, de certa maneira, a perspectiva do branco, além de também perpetuar a distância criada pelo sistema escravista e segregacionista dos Estados Unidos da América.
A contested uprising: William Styron and confessions of Nat Turner
Keywords: Literatura e história; William Styron; sistema escravagista; Literature and history; slavery system